Tooth Brushing Practices Among Bangladesh Rural Adolescents - Miah, MNA; Mia, MAQ; Haque, MM; Siingha, RK (Medicine Today, 2012)
DOI: http://dx.doi.org/10.3329/medtoday.v23i2.13099 Medicine TODAY Vol.23(2) 2011 pp.72-75